Reduced-Order Modeling for Mesoscale Reactor Design. Issue 8 (3rd August 2019) - Karnani, Sunny V.; Allmon, William; Waits, C. Mike
ABSTRACT: The following paper compares experiments with the performance of a simplified numerical model aimed at estimating surface temperatures of a mesoscale, combustion-driven, heat recirculating parallel channel reactor. Simplification is enabled by discretizing the domain of interest using a series of perfectly stirred reactors. This approach avoids the treatment of convective and diffusive transport and instead focuses on chemistry and heat transfer. An end user of the model is empowered to casually vary system parameters to satisfy a latent curiosity or as part of a larger parametric analysis, both of which are, otherwise, computationally expensive. Once designed, the reactor will serve as a heat source for a thermal-to-electrical energy convertor when coupled to a thermophotovoltaic receiver. All simulations are performed using Cantera: an open-source chemical kinetics library, which defines a set of abstracted forms to be used as building blocks to study the interaction between chemistry and heat transfer in a simplified geometry. The utility of this approach is demonstrated by assessing energy loss mechanisms through various surfaces, an impractical feat experimentally. The code developed as a part of this effort will be made available in an online repository.